Modeling of Water Seepage at Sindang Heula Dam - Kusumaningrum, Winda; Purnaditya, Ngakan Putu; Fathonah, Woelandari; Priyambodho, Bambang Adhi; Subekti, Subekti; Nabila, Firyaal (Jurnal Fondasi, 2024)
A embankment dam is a dam built by stockpiling materials such as stones, gravel, sand, and soil on a certain composition with the function of carrying or lifting the water surface contained in the reservoir [1]. One of the structural safety of a embankment dam is against water seepage. Water seepage that occurs on the slope body during flooding can affect the decrease in slope stability, where the seepage will cause piping symptoms [2]. This study aims to determine the seepage discharge value that occurs in the dam body. The object of this study was Sindang Heula embankment dam in Banten Province. The method used is to conduct an analysis using GeoStudio software with the SEEP/W feature for seepage discharge. Simulation run in two scenarios as steady state condition and transient. Both scenario also run at least on three reservoir water level conditions. They are water level during flood, normal water level and half of full water level. Steady state condition gave seepage flux about 3.773×10-6 m3/sec/m2 as maximum value. In another hand, 30 days transient simulation gave maximum value about 8.7188×10-4 m3/sec/m2 and it occurred in small reference time after initial run. This study infomed that SEEP/W has capability to simulate water flux through porous media of embankment dam.